2021
DOI: 10.7554/elife.69679
|View full text |Cite
|
Sign up to set email alerts
|

The influence of biological and lifestyle factors on circulating cell-free DNA in blood plasma

Abstract: Research and clinical use of circulating cell-free DNA (cirDNA) is expanding rapidly; however, there remain large gaps in our understanding of the influence of lifestyle and biological factors on the amount of cirDNA present in blood. Here, we review 66 individual studies of cirDNA levels and lifestyle and biological factors, including exercise (acute and chronic), alcohol consumption, occupational hazard exposure, smoking, body mass index, menstruation, hypertension, circadian rhythm, stress, biological sex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 126 publications
2
31
1
Order By: Relevance
“…The maternal peripheral blood chromosomes of case 10 were proven to have triple X and the maternal karyotype of case 11 was mos 46,XXX,rob(13;14)(q10;q10)[31]/45,XX,rob(13;14)(q10;q10)[19], which led to discordant results ( Table 5 ). Maternal SCA (full or mosaic) is a common and important cause of discordant SCA ( 1 , 27 ) because the majority of plasma cfDNA of pregnant women are derived primarily from cellular apoptosis of the hematopoietic system ( 28 ). Thus, determining the maternal karyotype would increase the accuracy of NIPT results for SCA ( 1 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The maternal peripheral blood chromosomes of case 10 were proven to have triple X and the maternal karyotype of case 11 was mos 46,XXX,rob(13;14)(q10;q10)[31]/45,XX,rob(13;14)(q10;q10)[19], which led to discordant results ( Table 5 ). Maternal SCA (full or mosaic) is a common and important cause of discordant SCA ( 1 , 27 ) because the majority of plasma cfDNA of pregnant women are derived primarily from cellular apoptosis of the hematopoietic system ( 28 ). Thus, determining the maternal karyotype would increase the accuracy of NIPT results for SCA ( 1 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…cirDNA has been of interest as an analyte in liquid biopsies since 1977, when it was first found to contain ctDNA [ 9 ]. In healthy individuals, cirDNA is present at low levels (10–15 ng/mL blood), though it does increase during tissue stress instigated by exercise, inflammation, or injury [ 10 ]. In cancer patients it can be up to 10-fold higher, especially with metastatic disease, partially due to ctDNA contribution [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of 25 studies that reported on the relationship between cfDNA and biological sex revealed a greater likelihood of increased cfDNA levels in males vs. females. However, these differences are considered to be minor and may reflect lifestyle differences between males and females, and as such requires further investigation [ 59 ]. Other variables such as haematocrit or cannula placement pain [ 60 ], height [ 61 , 62 ], and the menstrual cycle [ 63 , 64 ] were not found to affect total cfDNA levels.…”
Section: Measurement Of Total Cfdna Levels In Different Contextsmentioning
confidence: 99%
“…To-date, only two studies have investigated the effects of alcohol intake on total cfDNA levels, but no correlation was found [ 70 , 71 ]. However, more research is needed, as these studies had incomplete methodological reporting, used a non-specialized method for cfDNA isolation, failed to specify alcohol intake for subjects in the ‘moderate-severe’ category [ 71 ], have not in their cohort categorization accounted for possible differences between social drinkers and non-drinkers [ 70 ], and were performed in the context of a study on cancer [ 59 ].…”
Section: Measurement Of Total Cfdna Levels In Different Contextsmentioning
confidence: 99%
See 1 more Smart Citation